STRATEGI JURNALIS ISLAM DALAM DAKWAH DI ERA DIGITAL - Tijani, Naufal (AT-TAWASUL, 2025)
This study aims to analyze: how da'wah strategies are implemented in the digital era, and secondly: what is the role of Muslim journalists in developing da'wah. From these problems, the author collected relevant data using a qualitative approach, describing the problem as a research priority. The results of the study indicate that journalism can be defined as the activities of journalists in searching, collecting, and processing data to produce interesting news. These journalistic activities are then continued by disseminating it to the public through print, electronic, and digital media. Journalism is the art of covering, writing, and disseminating information, as well as a profession. Because in this profession, expertise and work are required according to their expertise so that the person receives compensation. The development of communication and information technology through the Internet has had an impact on changes in information distribution. Information distribution is increasingly rapid, and the audience also receives it quickly. Therefore, the role of Muslim journalists in developing da'wah, besides functioning as a tool for information, education, and entertainment, also as a spiritual guide or developing the mission of amar ma'ruf nahi munkar.